2000
DOI: 10.1002/1521-3765(20000901)6:17<3186::aid-chem3186>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Self-Penetration—A Structural Compromise between Single Networks and Interpenetration: Magnetic Properties and Crystal Structures of [Mn(dca)2(H2O)] and [M(dca)(tcm)], M=Co, Ni, Cu, dca=Dicyanamide, N(CN)2−, tcm=Tricyanomethanide, C(CN)3−

Abstract: The three-dimensional coordination polymers [Mn(dca)2(H2O)] (1) and [M(dca)(tcm)], M =Co (2), Ni (3), Cu (4), dca =dicyanamide, N(CN)2-, tcm = tricyanomethanide, C(CN)3-, have isomorphous structures. In 1 half the dca ligands coordinate directly (through all three nitrogen atoms) to three Mn atoms (all metal atoms are six-coordinate), while the other half coordinate to two Mn atoms (through the nitrile nitrogens) and hydrogen bond to water molecules coordinated to a third Mn atom (through the amide nitrogen). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(28 citation statements)
references
References 9 publications
2
26
0
Order By: Relevance
“…Investigation of metal-dca complexes {dca is dicyanamide, [N(CN) 2 ] À } is a fast-growing research field because of the large variety of topologies and magnetic properties shown by complexes of the dca ligand (Miller & Manson, 2001;Batten & Murray, 2003). It is a versatile ligand coordinating to metal ions in various modes: monodentate binding through one nitrile N atom (Marshall et al, 2000), end-to-end bridging through the two nitrile N atoms Jensen et al, 1999) and triply bridging three metal atoms using all three N donor atoms (Jensen et al, 2000;Kurmco & Kepert, 1998). These varied coordination possibilities allow the preparation of compounds with a variety of architectures, including mono-and dinuclear complexes, as well as one-, twoand three-dimensional network structures.…”
Section: Commentmentioning
confidence: 99%
“…Investigation of metal-dca complexes {dca is dicyanamide, [N(CN) 2 ] À } is a fast-growing research field because of the large variety of topologies and magnetic properties shown by complexes of the dca ligand (Miller & Manson, 2001;Batten & Murray, 2003). It is a versatile ligand coordinating to metal ions in various modes: monodentate binding through one nitrile N atom (Marshall et al, 2000), end-to-end bridging through the two nitrile N atoms Jensen et al, 1999) and triply bridging three metal atoms using all three N donor atoms (Jensen et al, 2000;Kurmco & Kepert, 1998). These varied coordination possibilities allow the preparation of compounds with a variety of architectures, including mono-and dinuclear complexes, as well as one-, twoand three-dimensional network structures.…”
Section: Commentmentioning
confidence: 99%
“…In a separate area, metal dicyanamide {dca, [N(CN) 2 ] À } coordination chemistry is a fast-growing research ®eld because of the interesting possibilities for coordination and physical properties that these complexes possess (Miller & Manson, 2001). Dicyanamide is a versatile ligand for coordinating to metal ions in various modes, such as monodentate bonding through a nitrile N atom (Marshall et al, 2000), end-to-end bridging through the two nitrile N atoms Jensen et al, 1999) and triply coordinating through its three N atoms, bridging three metal atoms (Jensen et al, 2000;Kurmco & Kepert, 1998). The coordination properties thus allow for the preparation of compounds with a large variety of architectures, both mononuclear and dinuclear, as well as one-, two-and three-dimensional networks.…”
Section: Commentmentioning
confidence: 99%
“…The topology of this network, based on six‐ and three‐connected nodes in the ratio 1:2, is the same of the prototypical rutile,12, 14 with Ru in the place of Ti and Ag in the place of O (see Figure 3, bottom left). Few other examples of coordination networks with this topology have been previously reported 16. The channels along [1 0 1] (Figure 3, top) contain solvated molecules of TCE and butanol (that are lost on heating the bulk samples above 120 °C).…”
Section: Methodsmentioning
confidence: 80%